Associação entre doença periodontal, hipertensão arterial, síndrome metabólica e proteína C - reativa ultrassensível em usuários do sistema público de saúde de Cuiabá-MT - Teixeira, Silvana de Faria Moreira (2013)
Periodontal disease is a worsening of the health of infectious etiology and inflammatory nature, characterized by destruction of the supporting tissues of the tooth through the direct action of bacteria, and action of the host. Studies have shown a relationship between periodontal disease and the onset or progression of some systemic diseases, including the cardiovascular. Objective: To analyze the association between periodontal disease, hypertension, metabolic syndrome and other laboratory variables of interest. Methods: An observational cross-sectional study in a sample of 177 adults and seniors who were attended at the sector screening of the four centers of dental specialties (CEO) of the Cuiaba’s Municipal Health from September to December 2012. Were administered surveys, conducted anthropometric measurements, blood pressure, clinical examination and laboratory tests of blood and urine. The criterion for diagnosis of hypertension adopted was: mean of two measurements of SBP ≥ 140 mmHg and / or DBP≥ 90 mmHg, or use of oral antihypertensive, metabolic syndrome according to " First Brazilian Guideline for Diagnosis and Treatment of Metabolic Syndrome " and NCEP - ATP III and periodontal diagnosis using the Community Periodontal Index. Results: The prevalence of periodontal disease was 72.3 %, Hypertension 40.6% and Metabolic Syndrome 33.3%. The per capita income of up to ½ minimum wage was associated with periodontal disease (p=0.026) in bivariate analysis . There was no association between periodontal disease and Metabolic Syndrome (PR= 0.98, 95% CI= 0.80- 1.19, p= 0.812). Increased waist circumference, low HDL cholesterol and hypertension had a higher relation with periodontal disease , but without statistical significance. Among the laboratory variables only high levels of ultrasensitive Creactive protein were significantly associated with periodontal disease both in bivariate analysis as multiple (PR= 1.22, 95% CI = 1.02-1.47, p = 0.030). Conclusions: High levels of ultrasensitive C-reactive protein were significantly associated with periodontal disease. It is suggested to carry out longitudinal studies broader, population-based to assess the relationship between periodontal disease and the variables analyzed.